Upper Limit Superior and Lower Limit Inferior of Soft Sequences - Hasan Hameed, Ahmed; Annon Mousa, Ekhlas; Abdullah hamad, Abdulsattar; ., . (International Journal of Engineering and Technology, 2018)
In this paper we have provided some of evidence work of the authors R.N.Hasan, O.A Tantawy in 2016 [1] thy given proof of the concept between two bound soft sets & subsets of soft elements real numbers also was concluded an upper bound and lower bound by using two sequences of soft element real numbers which is Â Â In this paper, supposed to extend R.N.Hasan, O.A Tantawy work but here we are given new notion and proof for upper limit superior and lower limit inferior with two sequences and subsequences for the conclude new proof after recalled that, which is upper limit superior and lower limit inferior By this we have proved above new two theorems and one proposition & strengthen the example. AMS Subject Classification: 06D72, 40A05, 54A40 Â Â